Differences in Cognitive-Perceptual Factors Arising From Variations in Self-Professed Paranormal Ability - Drinkwater, Kenneth Graham; Dagnall, Neil; Denovan, Andrew; Williams, Christopher (Frontiers in Psychology, 2021)
This study examined whether scores on indices related to subclinical delusion formation and thinking style varied as a function of level of self-professed paranormal ability. To assess this, the researchers compared three groups differing in personal ascription of paranormal powers: no ability, self-professed ability, and paranormal practitioners (i.e., Mediums, Psychics, Spiritualists, and Fortune-Tellers). Paranormal practitioners (compared with no and self-professed ability conditions) were expected to score higher on paranormal belief, proneness to reality testing deficits, emotion-based reasoning, and lower on belief in science. Comparable differences were predicted between the self-professed and no ability conditions. A sample of 917 respondents (329 males, 588 females) completed self-report measures online. Multivariate analysis of variance (MANOVA) revealed an overall main effect. Further investigation, using discriminant descriptive analysis, indicated that paranormal practitioners scored higher on proneness to reality testing deficits, paranormal belief, and emotion-based reasoning. Belief in science did not meaningfully contribute to the discriminant function. Overall, results were consistent with previous academic work in the domains of paranormal belief and experience, which has reported that paranormal-related cognitions and perceptions are associated with factors related to subclinical delusion formation (i.e., emotion-based/intuitive thinking).